Pemodelan Proses Bisnis Peternakan Ayam Petelur - Lailatul Fadilah; Fadillah Siva; Muhammad Zaim Maulana; Muhammad Ainul Yaqin (Jurnal Ilmiah Informatika, 2022)
Laying hens are all activities related to the production of laying hens from the chick stage to the adult stage. The business process of laying hens in general starts from the activities of the biosecurity system, breeding, rearing, housing, and the animal feed and health system. Based on three studies that have been carried out in the period 2017-2021, the business process of laying hens is still minimally modeled. The problem that arises when the laying hen's farm business process is not modeled is that many business activities are repeated and missed. Therefore, business process modeling needs to be done to improve coordination between process units. This research aims to model the business process of laying hens, which refers to Porter's value chain analysis. This study uses data taken from observations and interviews with local laying hens in Malang. The data used is related to details of business activities, the parties involved, and SOPs in the laying hens business. The method in this study uses the BPMN approach. This research begins with data collection, analysis of porter's value chains, analysis of the relationship between business processes, then denotes the process obtained with BPMN notation. This research produces a business process model for laying hens which BPMN denotes. This business process model can solve coordination problems in the laying hens business.